Peningkatan Performans Produksi Dan Kualitas Daging Pada Ayam Broiler Periode Finisher Yang Diberi Fitobiotik - A. Wardah; Rini Rahayu Sihmawati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2020)
The use of phytobiotics which can improve production performance and quality of broiler chicken meat continues to be done. The use of herbs that contain metabolic components is a very important strategy. This study aims to evaluate the production performance and quality of broiler chicken meat given phytobiotic drinks in the finisher period. The study was conducted experimentally using a completely randomized design with 4 treatments of phytobiotic drinks 0, 30, 60, and 90% in broiler chickens aged 25-40 days and repeated 5 times. The liquid phytobiotics used in the form of a mixture of Curcuma domestica powder are known as antioxidants, antimicrobials and anti-inflammatory properties. Curcuma domestica: Zingiber officinale: Kaempferia galanga: Curcuma zanthorrhiza: Syzygium polyanthum with a ratio of 1:1:1:1:2. The results showed that giving phytobiotics significantly (P <0.05) increased body weight, carcass weight and broiler feed consumption. The provision of 30% phytobiotics resulted in body weight, carcass weight and feed consumption significantly (P <0.05) compared to giving 0, 60 and 90% phytobiotics. The results of the analysis of the fat and cholesterol content of broiler meat that were given phytobiotics were significantly (P <0.05) lower than the fat content of broiler meat that was not given phytobiotics. The provision of 60% phytobiotics was significantly (P <0.05) lower than the provision of 0, 30 and 90% phytobiotics. While the results of the analysis of protein content of broiler meat given 60% phytobiotics were significantly (P <0.05) higher than those given 0, 30 and 90% phytobiotics. The results of this study can be concluded that the provision of phytobiotics can affect the production performance and quality of broiler chicken meat in the finisher period. Giving 30% phytobiotics can increase as much as 20% body weight, carcass weight and feed consumption. Meanwhile, giving 60% phytobiotics increased 78.58% of meat protein content and decreased 70.54% of meat fat and 75% of meat cholesterol. Keywords: Broiler chicken; finisher; production; meat quality.